2020
DOI: 10.1371/journal.pone.0241081
|View full text |Cite
|
Sign up to set email alerts
|

The effect of concurrent elevation in CO2 and temperature on the growth, photosynthesis, and yield of potato crops

Abstract: Global climate change accompanied by continuous increases in atmospheric carbon dioxide (CO 2) concentration and temperature affects the growth and yield of important crops. The present study investigated the effect of elevated temperature and CO 2 concentrations on the growth, yield, and photosynthesis of potato (Solanum tuberosum L. cv. Superior) crops using Korean Soil-Plant-Atmosphere-Research chambers that allow the regulation of temperature and CO 2 concentration under daylight conditions. Based on the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 66 publications
3
25
0
Order By: Relevance
“…Amelioration of high temperature effects by Elevated CO 2 . In the current study, the percentage inhibition of dry matter accumulation rate (DMAR) by high temperature was somewhat greater in Low CO 2 than in Elev CO 2 treatments (56 and 35%, respectively, at tuber initiation; and 32 and 15%, respectively, at tuber bulking), consistent with earlier findings [ 33 ]. In several studies, elevated CO 2 has been found to partly ameliorate high temperature stress [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Amelioration of high temperature effects by Elevated CO 2 . In the current study, the percentage inhibition of dry matter accumulation rate (DMAR) by high temperature was somewhat greater in Low CO 2 than in Elev CO 2 treatments (56 and 35%, respectively, at tuber initiation; and 32 and 15%, respectively, at tuber bulking), consistent with earlier findings [ 33 ]. In several studies, elevated CO 2 has been found to partly ameliorate high temperature stress [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…Whole-plant dry matter accumulation rate, a measure of whole plant photosynthesis in excess of respiration, was inhibited by high temperature about twice as much at the stage of tuber initiation than at tuber bulking (Table 1; Figures 1 and 2). Similar findings were obtained in studies of elevated temperature under field conditions with temporary transparent chambers in which temperature was increased by about 4 • C for discrete periods of time [32,33]. Moreover, studies that involved treatments with 35 • C stress, similar to the present investigation, showed that tuber growth was strongly decreased by exposure to 35 • C at early phase of tuberization but had a diminishing effect at later stages [26].…”
Section: High Temperature Stress Effect On Whole Plant Biomass Accumulationsupporting
confidence: 89%
See 1 more Smart Citation
“…Elevated CO 2 stimulates the root and shoot growth of wheat, but this stimulation was found to reduce when plants were grown in combined elevated temperature and elevated CO 2 [30]. Lee et al [31] showed that while elevated temperatures may negatively influence the growth and yield of potato crops, concurrent and appropriate elevation of CO 2 and temperature can promote balanced development of source and sink organs and positively affect potato productivity. Field experiments on sunflower production using an OilCROP-SUN model predicted that the increase in temperature negatively affects sunflower productivity in Pakistan.…”
Section: Effects Of Elevated Co 2 and Elevated Temperatures On Sunflower Plants Growthmentioning
confidence: 99%
“…It is known that higher temperatures are always accompanied by elevated atmospheric CO 2 concentrations (Lee et al, 2020), and the global mean surface temperature is expected to rise by 1–4.5°C, depending on the scenario, by the year 2100 (IPCC, 2013). Few case studies have explored the effects of elevated CO 2 and elevated temperature on herbivore performance in such a way that both individual and combined effects of these two factors could be evaluated (Zvereva & Kozlov, 2006).…”
Section: Introductionmentioning
confidence: 99%